Synthesis and Characterization of Gold Nanoparticles Using Trisodium Citrate as a Reductant - Astriana Dewi; Suriati Eka Putri; Pince Salempa (Universitas Negeri Gorontalo, 2020)
This research is an experimental study that aims to determine the characteristics of gold nanoparticles (Au-NPs) synthesized using trisodium citrate as a reducing agent. 0.4 mM HAuCl4 solution was synthesized using Na3C6H5O7 to convert Au3+ to Au0 with several variations of the reducing agent concentration, 3.5%; 5%; 6.5% and 8%. Determination of reaction time was measured using a UV-Vis spectrophotometer with time variations of 1, 5, 15, 30 and 45 minutes. Characterization of the size and lattice of Au-NPs crystals using X-Ray Difraction (XRD) and morphological characterization using Scanning Electron Microscopy (SEM). The results of the characterization, Au-NPs were produced blackish brown in color, and yields were 66.13%, 89%, 59.63% and 50.30% respectively for trisodium citrate reductant concentrations of 3.5%; 5%; 6.5% and 8%, with an average Au-NPs size of 46.97; 19.06; 50.03 and 39.68 nm, Face Centered Cubic (FCC) Crystal lattice and have a homogeneous morphology.